Postoperative topical analgesia of hemorrhoidectomy with policresulen and cinchocaine: a prospective and controlled study - Froehner Junior,Ilario (2014)
OBJECTIVE: To evaluate the effects of topical policresulen and cinchocaine in the postoperative pain behavior of open hemorrhoidectomy.METHODS: We conducted a prospective, double-blinded, controlled study. The control group received the usual guidelines with oral medications. The topical treatment group received, in addition, the application of the ointment and was comprised of two subgroups (policresulen + cinchocaine, and placebo). Pain intensity was recorded with the visual analogue scale.RESULTS: 43 patients were operated on: control group - n = 13, one excluded; placebo - n = 15; and policresulen + cinchocaine - n = 15. The mean age was 45.98 years and 37.2% were men. The average pain intensity was 4.09 (immediate postoperative), 3.22 (hospital discharge), 5.73 (day 1) , 5.77 (day 2), 5.74 (day 3), 5.65 (day 7), 5.11 (day 10), 2.75 (day 15) and 7.70 (first bowel movement), with no difference between groups in all periods.CONCLUSION: This study showed no reduction in pain after hemorrhoidectomy with the use of topical policresulen and cinchocaine.